GRAVITATION, FORCE, AND TIME - James Arnold (European Scientific Journal, ESJ, 2013)
Gravitation is described as a uniquely geometric phenomenon, incompatible with the concept of force, and only analogically comparable with force by means of mathematical formalisms. Two thought experiments are employed to demonstrate that the association of gravitation with force is irreconcilable with the geometric interpretation, and without theoretical foundation or empirical support. Motion in time is identified as the dynamic source of what has been attributed as the energetic component of gravitational phenomena.